2021
DOI: 10.1590/1807-3107bor-2021.vol35.0130
|View full text |Cite
|
Sign up to set email alerts
|

Survival of atraumatic restorative treatment restorations in the elderly patients: a systematic review

Abstract: This study aimed to assess the survival of glass ionomer cement (GIC) restorations performed using the atraumatic restorative treatment (ART) in elderly patients. The systematic review protocol was registered in the PROSPERO database. The records were searched until August 2020 in eight electronic bibliographic databases, and included randomized and non-randomized clinical trials and observational studies, with no restrictions on the language or year of publication. Study selection and data extraction were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…RMGICs seems to be a very good option in restoring Class I and II cavities and performed better than HVGIC and composite resins in some studies in terms of survival rates, uoride release and biologic considerations (43,46,48). Other studies could not nd signi cant differences between RMGICs compared to conventional GICs, composite resins, compomers and amalgam (45,46,47,48,54) or there's con icting evidence on which performs better between RMGICs and composite resins. Silver-reinforced glass ionomer cement seems to have the lower survival rates and higher recurrences of secondaries caries (46).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…RMGICs seems to be a very good option in restoring Class I and II cavities and performed better than HVGIC and composite resins in some studies in terms of survival rates, uoride release and biologic considerations (43,46,48). Other studies could not nd signi cant differences between RMGICs compared to conventional GICs, composite resins, compomers and amalgam (45,46,47,48,54) or there's con icting evidence on which performs better between RMGICs and composite resins. Silver-reinforced glass ionomer cement seems to have the lower survival rates and higher recurrences of secondaries caries (46).…”
Section: Discussionmentioning
confidence: 98%
“…In primary dentition the ART technique can be effective because it helps in reducing the anxiety of the patients (44,45,53). Despite is wide application in primary dentition, two studies found that the annual failure rates (AFRs) of ART were higher in primary dentition compared to permanent in both single and multi-surface restorations (44,48).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this step, 11 studies were excluded for the following reasons: (1) not being a systematic review of clinical trials and (2) not evaluating clinical performance/longevity of GICs. Finally, 13 studies [48][49][50][51][52][53][54][55][56][57][58][59][60] were included in the following review. The study selection process is shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%